THE ROLE OF BRAND POSITIONING AND BRAND EXPERIENCE IN INCREASING PARENTAL SOCIALIZATION AND BRAND LOYALTY: A STUDY ON MOTORCYCLE BRANDS IN INDONESIA - Sutisna, Sutisna; Wiguna, Wahyu (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This study aims to investigate the role of brand positioning and brand experience as an antecedent for parent socialization and brand loyalty. This research is quantitative. The product brands studied are Yamaha, Honda and Suzuki motorcycles marketed in Indonesia. The respondents of this study were 414 respondents spread across West Java and Banten Provinces. The data analysis method uses the structural equation model (SEM-PLS). The study results show that Brand positioning and brand experience plays a role in improving parent socialization and brand loyalty.Socialization from parents to children plays a role in increasing brand loyalty. This research can add insight into how brand positioning is very important and should be done consistently because it will impact parent socialisation and customer loyalty